VIOLENCE RISK ASSESSMENT IN PSYCHIATRY - LITERATURE REVIEW AND PRACTICE COMPARISON BETWEEN LATVIA AND GERMANY - Konstantinova, Karina; Kuznecova, Alina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Evidence-based future community violence risk assessment is a crucial issue in psychiatry. It is a cornerstone of safeguarding the rights of persons with mental health issues. Authors aimed to analyse the modern methods of risk assessment in psychiatry and the current practice and legal framework. Authors undertook a scoped review of the literature with search terms related to future community violence risk prediction for mentally disordered offenders in Latvian, English, German, and Russian languages. Main difficulties in future community violence risk assessment are demonstrated via Latvia’s court decisions analysis. Marked differences were identified: there are no standardized methods available/registered in Latvia, therefore risks assessment is performed via clinical assessment only. In Germany, the risk assessment is performed via structured evidence – based risk assessment tools and clinical assessment; nevertheless, the choice of the assessment tool remains challenging.